Langmuir-Blodgett films of binary mixtures for polymethylmethacrylate/rubrene and stearic acid/rubrene: formation conditions and optical properties - Bezkrovnaya, O.N.; Savin, Yu.N.; Dobrotvorskaya, M.V. (Functional Materials, 2006)
Polymorphism of polymethylmethacrylate/rubrene and a stearic acid/rubrene monolayers depending on concentration of luminophore immobilized in the film has been studied. The maximum rubrene concentration has been determined at which phase separation in monolayers of the binary systems is not observed. It is revealed that in multilayer Langmuir-Blodgett films with immobilized rubrene molecules, its content is higher in the polymer film than in stearic acid. The rubrene concentration in Langmuir-Blodgett films of polymethylmethacrylate grows linearly with increasing carry pressure. It is found that at exposure of films in bidistilled water at 22°C for 45 min, the luminophore content in the films decreases by at most 40 %.